2000
DOI: 10.1289/ehp.00108s2215
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of trichloroethylene and its metabolites: implications for the risk assessment of trichloroethylene.

Abstract: This article addresses the evidence that trichloroethylene (TCE) or its metabolites might mediate tumor formation via a mutagenic mode of action. We review and draw conclusions from the published mutagenicity and genotoxicity information for TCE and its metabolites, chloral hydrate (CH), dichloroacetic acid (DCA), trichloroacetic acid (TCA), trichloroethanol, S-(1,2-dichlorovinyl)-L-cysteine (DCVC), and S-(1,2-dichlorovinyl) glutathione (DCVG). The new U.S. Environmental Protection Agency proposed Cancer Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…The 2005 bioassay was negative at a dose that should have produced a small, but significant increase in tumor incidence if a linear low dose extrapolation were applied to the results of the corn oil gavage study. While DCA have been found genotoxic in some studies, the concentrations necessary to produce 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 30 these effects are so high relative to the systemic concentrations that produce cancer in animals as to make them irrelevant to in vivo carcinogenesis (Moore and Harrington-Brock, 2000). This conclusion is bolstered by the fact that DCA has been shown to selectively stimulate the growth of already initiated cells (Stauber and Bull, 1997), which can completely account for the development of liver cancer (Miller et al, 2000) at much lower systemic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The 2005 bioassay was negative at a dose that should have produced a small, but significant increase in tumor incidence if a linear low dose extrapolation were applied to the results of the corn oil gavage study. While DCA have been found genotoxic in some studies, the concentrations necessary to produce 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 30 these effects are so high relative to the systemic concentrations that produce cancer in animals as to make them irrelevant to in vivo carcinogenesis (Moore and Harrington-Brock, 2000). This conclusion is bolstered by the fact that DCA has been shown to selectively stimulate the growth of already initiated cells (Stauber and Bull, 1997), which can completely account for the development of liver cancer (Miller et al, 2000) at much lower systemic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review it is concluded that the data on the mutagenicity of TCE indicate that neither TCE nor any of its major metabolites (chloral hydrate, dichloroacetic acid, trichloroacetic acid, and trichloroethanol) are potent genotoxic agents. However, the minor metabolite, dichlorovinylcysteine, that is formed locally in the kidneys of humans, mice, and rats, has been shown to be potent in inducing point mutations (in vitro) (Moore and Harrington-Brock, 2000).…”
Section: Toxicological Backgroundmentioning
confidence: 99%
“…In an article in this monograph, DCA is characterized as genotoxic only at high dose levels well above those expected at environmental exposure levels (39). Several hypotheses regarding the mechanism of carcinogenic action of TCE suggest underlying processes that might be markedly nonlinear.…”
Section: Pharmacokinetic Models and Internal Dosesmentioning
confidence: 99%
“…Neither TCE nor TCA appears to be genotoxic, and the evidence on CH is debated, as there is some evidence that it can act as a clastogen (16,39). In an article in this monograph, DCA is characterized as genotoxic only at high dose levels well above those expected at environmental exposure levels (39).…”
Section: Pharmacokinetic Models and Internal Dosesmentioning
confidence: 99%
See 1 more Smart Citation